1977
DOI: 10.3758/bf03199682
|View full text |Cite
|
Sign up to set email alerts
|

Failure of additivity in bisection of length

Abstract: Subjects were intructed to select one rod to lie halfway in length between two given rods. These bisection instructions imply an additive model in the subjective metric. However, the data were inherently nonadditive; the length of the bisector could be an increasing or a decreasing function of the length of one given rod, depending on the length of the other given rod. A convexity analysis and a nonmetric analysis both showed that no monotone transformation could make the data additive. The bisection problem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…And, there are numerous cases in which relative preferences are not decomposable into component attitudes at all. For example, intransitive relative preferences, violating unidimensionality, have been demonstrated repeatedly (e.g., Bar-Hillel & Margalit, 1988;Birnbaum, 1992;Shafir, Osherson, & Smith, 1990;Tversky, 1969) as have sub-or super-additivity (Anderson, 1977). Also, Hsee, Loewenstein, Blount, and Bazerman (1999) identified circumstances in which most participants preferred object A to object B when considered separately, while B was preferred to A in a relative comparison.…”
Section: Relative Preference ≠ Additive Differencementioning
confidence: 97%
“…And, there are numerous cases in which relative preferences are not decomposable into component attitudes at all. For example, intransitive relative preferences, violating unidimensionality, have been demonstrated repeatedly (e.g., Bar-Hillel & Margalit, 1988;Birnbaum, 1992;Shafir, Osherson, & Smith, 1990;Tversky, 1969) as have sub-or super-additivity (Anderson, 1977). Also, Hsee, Loewenstein, Blount, and Bazerman (1999) identified circumstances in which most participants preferred object A to object B when considered separately, while B was preferred to A in a relative comparison.…”
Section: Relative Preference ≠ Additive Differencementioning
confidence: 97%
“…And, there are numerous cases in which relative preferences are not decomposable into component attitudes at all. For example, intransitive relative preferences, violating unidimensionality, have been demonstrated repeatedly (e.g., Bar-Hillel & Margalit, 1988;Birnbaum, 1992;Shafir, Osherson, & Smith, 1990;Tversky, 1969) as have sub-or superadditivity (Anderson, 1977). Also, Hsee, Loewenstein, Blount, and Bazerman (1999) identified circumstances in which most participants preferred object A to object B when considered separately, while B was preferred to A in a relative comparison.…”
Section: Statementioning
confidence: 98%
“…It is worth noting that Anderson (1977) found that for lengths of rods the bisection of 2-variable model failed. Yet, contrary to his finding, our Experiment 1 validated a 3-variable bisymmetry model.…”
Section: Instructionmentioning
confidence: 98%
“…Taking a random sample of subjects and allowing random discrepancies from the equality of bisymmetry, then e.g., by applying the t-test or Wilcoxon-test (depending on the distributional assumptions of the difference), it is possible to test whether bisymmetry holds in the population represented by the sample. It is worth noting that in the context of information integration, 2-variables bisection is tested by variants of monotone analysis of variance (see experiments in, e.g., Carterette & Anderson, 1979;Anderson, 1977;Weiss, 1975). Mokken, (1993, 2000) observed that the equation of 2-variables bisymmetry (2) can be written in a matrix design form (see Fig.…”
Section: Bisymmetry For N Stimulimentioning
confidence: 99%